The Model of Non-Structural Mitigation Policy to the Landslide Prone Residential Areas in Lebong, Bengkulu - Iskandar Iskandar; Tri Andika; Wulandari Wulandari (Yuridika, 2021)
This study aims to find a model of non-structural disaster mitigation policies for landslide-prone settlements in Lebong Regency. The study is a sociological juridical (sociolegal). Processing and analysis of primary data, secondary data, information from the focus group discussion and legal documents were carried out in a descriptive qualitative manner. The results of the study show that the implementation of non-structural mitigation policies for residential areas prone to landslides has not been implemented optimally. There are internal and external obstacles to implementing such non-structural mitigation policies. The Lebong Regency government needs to formulate and determine community-based policy steps that include: identifying and mapping potential landslide residential areas, increasing community preparedness, increasing community knowledge and capacity, monitoring continuity towards landslide-prone settlements, implementing control/enforcement, maintaining the environmental balance, paying attention to the carrying capacity and amperage of the environment, compiling planning and budgeting, integrating disaster education in primary and secondary school curricula, strengthening regulatory frameworks and establishing mitigation standard operating procedures.